Rhetorical Allegory in the Light of Various Rhetorical Approaches - Zeinab Akbari; Raja Abuali (مطالعات زبانی و بلاغی)
The term "Balāḡat" in Islamic literature and its equivalent in the literary tradition of the West, the term "Rhetoric", has had three main meanings up to the present time: the first meaning is the Aristotelian understanding of rhetoric, which is condoned with the which relates to the Rhetoric and techniques and means of the audience's persuasion; Second, is the aesthetic or literary meaning connects rhetoric with poetry and techniques of imagination; and finally a new approach to rhetoric that tries to extend the scope of this science in such a way that the two previous concepts are combined together. "Allegory" is one of the rhetorical tools that have taken into account all approaches in the history of rhetoric. In other words, the aesthetic and persuasive capacities of allegory have led to pay attention to the works of rhetoric with various contributions to the concept of rhetoric. The purpose of this research is to redefine the various rhetoric's definitions and perspectives on allegory and explain its rhetorical power in the light of various approaches to rhetoric.